Effect of three different solutions used in patients with hematological malignity on oral mucositis - Harman, Merve; Ovayolu, Nimet; Ovayolu, Özlem (Nature Publishing Group, 2017)
[Abstract Not Available]
Keywords: Hematological Malignity; Oral Mucositis; Solutions